Hypoglycaemia in adults with insulin‐treated diabetes in the UK: self‐reported frequency and effects. Issue 8 (7th September 2015) - Frier, B. M.; Jensen, M. M.; Chubb, B. D.
Abstract: Aim: Few real‐life studies of non‐severe (self‐treated) hypoglycaemic events are available. This survey quantified the self‐reported frequency of non‐severe hypoglycaemia and its effects in adults with insulin‐treated diabetes in the UK. Methods: Adults aged > 15 years with Type 1 diabetes or insulin‐treated Type 2 diabetes completed ≤ 4 weekly questionnaires (7–day recall). Respondents with Type 2 diabetes were grouped by insulin regimen: basal‐only, basal–bolus and 'other'. Results: Overall, 1038 respondents (466 with Type 1 diabetes, 572 with Type 2 diabetes) completed 3528 questionnaires. Mean numbers of non‐severe events per week were 2.4 (Type 1 diabetes; median = 2) and 0.8 (Type 2 diabetes; median = 0); 23% and 26% of non‐severe events occurred at night, respectively. Fatigue and reduced alertness were the commonest issues following events (78% and 51% of respondents, respectively). The effects of nocturnal events persisted longer than those of daytime events: Type 1 diabetes = 10.6 vs. 4.9 h ( P  = 0.0002); Type 2 diabetes = 15.3 vs. 5.1 h ( P  < 0.0001). In the week following an event, respondents' blood glucose measurements increased by 4.3 (Type 1 diabetes; 12% increment) and 4.2 (Type 2 diabetes; 21% increment) tests/week. In employed respondents, 20% of events caused work‐time loss, more so following nocturnal (vs. daytime) hypoglycaemia: Type 1 diabetes = 2.7 vs. 1.1 h ( P  = 0.0184); Type 2 diabetes = 2.5 vs. 1.6 h ( P  = 0.1340). Most respondents rarely/never informed healthcare professionals about events (Type 1 diabetes = 82%, Type 2 diabetes = 69%). Conclusions: Non‐severe hypoglycaemia is common in adults with insulin‐treated diabetes in the UK, with consequent health‐related/economic effects. Communication about non‐severe hypoglycaemia is limited and the burden of hypoglycaemia may be underestimated. What's new?: A fifth of non‐severe hypoglycaemia episodes result in loss of work‐time. Nocturnal hypoglycaemia has a greater impact on work the next day (through time lost, rescheduling of the working day and difficulty concentrating) than daytime hypoglycaemia, particularly in Type 1 diabetes. Non‐severe episodes (particularly nocturnal) stimulate a short‐term increase in the frequency of blood glucose testing. Many adults with diabetes in the UK seldom, or never, inform healthcare professionals about non‐severe events, resulting in underestimation of the frequency and potential morbidity of hypoglycaemia.